ANALISIS STRUKTUR MODAL,PERTUMBUHAN PERUSAHAAN DAN KEBIJAKAN DIVIDEN UNTUK MENINGKATKAN NILAI PERUSAHAAN PADA PT TIMAH (PERSERO), TBK YANG TERDAFTAR DI BURSA EFEK INDONESIA - Lestari, Suci; Siahaan, Yansen; Susanti, Elly; Supitriyani, Supitriyani (Sekolah Tinggi Ilmu Ekonomi Sultan Agung Pematangsiantar, 2018)
The purpose of this research is 1. To find out the description of capital structure, company growth, and dividend policy to increase the value of the company at PT Timah (Persero), Tbk which are listed on the Indonesia Stock Exchange. 2. To find out the factors that caused the company's value to PT Timah (Persero), Tbk to decline. This research was conducted using qualitative descriptive techniques, comparative analysis techniques and inductive analysis techniques. In this research the type of data used are qualitative data and quantitative data. In this research the data source used is secondary data. The technique data collection used is documentation technique. From the results of this study can be concluded that 1. The average capital structure tends to increase, company growth tends to decrease, dividend policy and company value tend to decrease. 2. capital structure increases due to increased long-term debt but not followed by company value, company growth decreases due to increased inventory but not followed by firm value, dividend policy decreases due to retained earnings more than profit distributed to investor as dividend.The results of the study suggest that companies should reduce the use of long-term debt in carrying out their company operations and improve asset management and increase dividend policy to attract the attention of potential investors to invest in the company